Nurse educator competence in four European countries-A comparative cross‐sectional study - Imane Elonen; Satu Kajander‐Unkuri; Maria Cassar; Laia Wennberg‐Capellades; Susanne Kean; Tomáš Sollár; Terhi Saaranen; Miko Pasanen; Leena Salminen (Wiley, 2023)
Abstract Aim The aim of this article is to describe and compare the nurse educator competences in four European countries using three different evaluators: nurse educators (n = 329), heads of a nursing subject (n = 60) and student nurses (n = 1058). Design The study was conducted as a comparative cross‐sectional survey in Finland, Malta, Slovakia and Spain between May 2021 and February 2022. Methods The data were collected with an online survey. The instrument used was a 20‐item Tool for Evaluation of Requirements of Nurse Teachers, utilizing a 5‐point Likert‐type scale. The data were analysed statistically and reported according to STROBE guidelines. Results Nurse educators' competence evaluated positively in all the groups of evaluators, with a mean of >3.5. The self‐evaluation of nurse educators' competence was higher than the other evaluators' evaluations. Having a degree in nursing, having completed some pedagogical studies and longer work experience as a nurse educator had a positive association with higher self‐evaluated competence among nurse educators. Conclusions Nurse educator competence is at a good level in the selected European countries, but further studies are required to find the reasons behind the differences in evaluations. Public Contribution Each participating educational institution named a contact person who distributed the surveys to the participants and returned the study's metadata to the researchers.